Electrospun antibacterial polyacrylonitrile nanofiber membranes functionalized with silver nanoparticles by a facile wetting method. (November 2018) - Kharaghani, Davood; Kee Jo, Yun; Khan, Muhammad Qamar; Jeong, Yeonsu; Cha, Hyung Joon; Kim, Ick Soo
Graphical abstract: Highlights: PAN nanofibers with a surface functionalized by loading AgNPs were prepared. The nanofibers exhibit the appreciable antibacterial efficiency. Nanofiber membranesalso revealed good biocompatibility with mammalian cells. Abstract: Nanofiber membranes for biomedical filtration devices require antibacterial activity to prevent bacterial contamination under moisture conditions while exhibiting biocompatibility. Here, we propose an antibacterial membrane filter composed of electrospun polyacrylonitrile (PAN) nanofibers with a surface functionalized with silver nanoparticles (AgNPs) by a facile wetting process for in situ silver reduction under physiologically mild conditions. Sequential wetting of thermally stabilized PAN nanofibers in silver nitrate (AgNO3 ) and sodium hydroxide (NaOH) solutions enabled direct control of the amount of synthesized AgNPs and their release behaviors in an aqueous environment. The fabricated AgNPs-functionalized PAN nanofibers (PAN-AgNPs) exhibit the appreciable antibacterial efficiency against Escherichia coli and Staphylococcus aureus bacteria with considerable sustainability for repetitive use. In addition, the generated AgNPs on PAN nanofiber membranes in an adequate loading range also revealed good biocompatibility with mammalian cells. Thus, PAN-AgNPs nanofibers can be practically applied as a promising disinfecting membrane filter for biomedical and hygienic applications.